"Ekumenistička" politika Katoličke crkve u Crnoj Gori (1965. – 1970.) The "Ecumenical" Politics of the Catholic Church in Montenegro (1965–1970) - Papović, Dragutin (2021)
U članku se govori o utjecaju odluka Drugoga vatikanskoga koncila na djelovanje Katoličke crkve (Barske nadbiskupije i Kotorske biskupije) u Crnoj Gori. Ekumenizam, ili borba za ujedinjenje kršćanskih crkava, bio je jedan od glavnih zaključaka toga koncila. Ekumenska politika došla je do izražaja u drugoj polovini šezdesetih godina i imala je važnu ulogu u aktivnostima Katoličke crkve u Crnoj Gori. Na taj se način pokušala približiti Srpskoj pravoslavnoj crkvi, a zatim i Islamskoj zajednici i nametnuti im svoje stavove. To je dovelo do intenziviranja vjerskoga života, do novih odnosa između vjerskih zajednica i socijalističkoga režima i do promjena u međunacionalnim odnosima. Ta politika odrazila se i na unutrašnje odnose u Barskoj nadbiskupiji i Kotorskoj biskupiji. Članak je nastao na temelju prvorazrednih arhivskih izvora iz fonda Republičke komisije za vjerska pitanja Crne Gore.
The ecumenical initiative of the Catholic Church was one of the main outcomes of the Second Vatican Council. Ecumenism aimed for the unification of Christian churches, partnership with other religious communities, and a conciliatory relationship with the socialist regime. In this period, the traditional tolerance between religious communities was practised and the Church established relatively good relations with the government of Montenegro. This is why the Catholic Church in Montenegro embraced ecumenism, which was expressed through the work of the Archdiocese of Bar and the Diocese of Kotor. The Archbishop of Bar, Aleksandar Tokić, and the Apostolic Administrator of the Diocese of Kotor, Gracija Ivanović, made a personal contribution to this initiative. They established close ties with the Orthodox Metropolitan of Montenegro and the Littoral, Danilo Dajković, and the President of the Islamic Community (IC) in Montenegro, Šukrija Bakalović. They succeeded in engaging the Orthodox and Islamic leaders in Catholic religious celebrations, while the Catholic priests attended the religious celebrations of the Orthodox and the Muslims. The Montenegrin authorities had their representatives participate in these ceremonies too. This was all prompted by Catholic ecumenism, while the ecumenical strivings of the Catholic Church in Montenegro were also encouraged by the Vatican, i.e. the highest representatives of the Holy See and Pope Paul VI. The ecumenism of the Catholic Church in Montenegro had special features. It was of pro-Yugoslav orientation. It respected the religious, national, and traditional characteristics of Montenegro, and aimed for a partnership with the socialist regime. Archbishop Tokić and Administrator Ivanović also felt a strong attachment to Montenegro and Yugoslavia, and therefore cultivated a genuine friendship with the Orthodox and the Muslim population. Despite the sincere efforts and initial enthusiasm, their ecumenism failed because the Se
Bibliografija
Summary.
Keywords: Drugi vatikanski koncil; ekumenizam; Katolička crkva; Crna Gora; Barska nadbiskupija; Kotorska biskupija; nadbiskup Aleksandar Tokić; apostolski administrator Gracija Ivanović